2014
DOI: 10.1007/s13593-014-0259-9
|View full text |Cite
|
Sign up to set email alerts
|

A 1961–2010 record of fertilizer use, pesticide application and cereal yields: a review

Abstract: Global crop production has doubled since the Green Revolution on the average, but crop yield has stagnated or even declined in some regions. In the same time, food demand has highly increased due to population growth and higher living standards. The use of pesticides and mineral fertilizers has improved crop yields but also contaminated food and the environment, thus leading to a global food crisis. Here, we reviewed the historical trends of global pesticide and fertilizer application, cereal yields, and produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
89
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 168 publications
(106 citation statements)
references
References 48 publications
3
89
0
1
Order By: Relevance
“…Due to different national policies and/or regional resources, the consumption of chemical fertilizer and pesticide in agricultural production is imbalance (MacDonald et al 2011;Vitousek et al 2009). Most of countries in Eastern Asia has a phosphorus surplus but phosphorus scarcity is widespread in South America (Liu et al 2014;MacDonald et al 2011). Similarly, nitrogen surpluses are common in most Asian countries, while 80 % of African countries are nitrogen deficient (Liu et al 2010a;Vitousek et al 2009).…”
Section: Environmental Impacts Of Agricultural Practicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to different national policies and/or regional resources, the consumption of chemical fertilizer and pesticide in agricultural production is imbalance (MacDonald et al 2011;Vitousek et al 2009). Most of countries in Eastern Asia has a phosphorus surplus but phosphorus scarcity is widespread in South America (Liu et al 2014;MacDonald et al 2011). Similarly, nitrogen surpluses are common in most Asian countries, while 80 % of African countries are nitrogen deficient (Liu et al 2010a;Vitousek et al 2009).…”
Section: Environmental Impacts Of Agricultural Practicesmentioning
confidence: 99%
“…However, this prediction did not consider the potential impacts of current agricultural practices on crop production in the future, although the environmental impacts of agricultural systems raise concerns. The impacts and limits of fertilizer and insecticide applications have raised public concerns about the sustainability and security of food supplies (Liu et al 2014;Pingali 2012). Several studies indicated that common 44 pesticides can increase foraging failure and death in honey bees, and can inhibit colony growth and production of queens (Henry et al 2012;Whitehorn et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Since the beginning of the 1980s, fertilizer consumption in China has grown intensively, with an average annual 3-5% growth, and the fertilizer use per unit area has been close to 4 times the global fertilizer use [24]. In China, the total consumption of nitrogen, phosphorus, and potash increased to 54.16 million tons from 0.73 million tons from 1961 to 2015, and this increasing trend is expected to continue in the following decades [25]. Data from the National Bureau of Statistics show that the fertilizer use associated with China's grain production accounted for more than 80% of China's fertilizer production in 2013.…”
Section: Introductionmentioning
confidence: 99%
“…Based on reviews of global trends affecting current food production systems worldwide (Nansen and Ridsdill-Smith 2013;Bon et al 2014;Liu et al 2014;Popp et al 2013), it is predicted that a wide range of agricultural and horticultural production systems will face an increase in pest pressures and therefore also in numbers of pesticide spray applications (Bon et al 2014;Liu et al 2014;Martínez-Blanco et al 2013) (Fig. 1a).…”
Section: Introductionmentioning
confidence: 99%
“…Although exact figures are not available for many countries, there are fairly sobering estimates of the global use and applications of pesticides. Liu et al (2014) calculated that, on an annual basis, at least 20 countries apply over 2 kg of insecticides per hectare of harvested agricultural land. The annual pesticide market has been estimated to be worth approximately USD 0.9 billion in Africa alone (Bon et al 2014) and approximately USD 40 billion globally (Popp 2011;Popp et al 2013).…”
Section: Introductionmentioning
confidence: 99%